SIMULASI DAN PERANCANGAN JARINGAN TEKNOLOGI VLAN DI ESCÃLA TÃCNICO AGRÃCOLA DE NATARBORA MENGGUNAKAN PACKET TRACER 6.0 - Boavida, Abreu Andre; Triyono, Joko; Sutanta, Edhy (Jurnal Jarkom, 2013)
ABSTRACTTÃ©cnico AgrÃcola De Natarbora is one of the State Agricultural School which is located in the Democratic Republic of Timor-Leste, along with the increasing need for information and technology, the school requires the development of a computer network that can be developed easily and flexibly.Â Simulation and design of network technology of VLAN in the TÃ©cnico AgrÃcola De Natarbora using packet tracer. Efforts to overcome these problems continue to be undertaken by many parties.Â One alternative that can be used is an attempt to use technology Virtual Local Area Network (VLAN), with the hope of providing better results compared to LAN.Â VLAN is a logical function of the switch, which is a special function that is configured to use the software.Â This function will divide the network into several virtual networks that are physically still connected to the same switch.Â With this function, the computer network can be made without depending on its physical location, but based on the needs and functions. VLAN can be used to create a flexible network setting by segmenting the department in accordance with company and can only do a broadcast on a particular group without depending on the location of the workstation. Â Keywords: LAN, VLAN, network performance.